Life story and academic studies of prof. dr. ahmet noyan - Nigar Yerlikaya; Özgül Küçükaslan (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out in order to reveal the scientific life story of 103 year old Prof. Dr. Ahmet Noyan, who left a mark in the veterinary profession, as well as to contribute to the biography archive of veterinary medicine. Materials and Methods: Prof. Dr. Ahmet Noyan's personal files in the archive of Ankara University Faculty of Veterinary Medicine and original documents in his private archive were created. Missing information on the subject was completed by interviewing face to face. The information obtained from the document analysis was evaluated retrospectively and transcribed. Identification of archive documents and necessary explanations are given in footnotes. Results: Professor Dr. Ahmet Noyan who is a doyen academician of physiology which is one of the basic constituents of Turkish Veterinary Medicine; graduated from the HAI VF in 1940, and took up a position as an assistant in 1943. After completing his graduate education in the USA in 1949, Noyan returned to his country, became an associate professor in 1951 and a professor in 1961. Since 1973 he has continued his studies in the Department of Physiology at HUFM of Science Department of Biology. Noyan, who has been involved in many scientific and professional activities in national and international fields for more than 40 years in his professional life, retired in 1984. His book named "Physiology in Life and Medicine", which is described as an extraordinary example of success in his field, has become one of the bookmarks of medical and veterinary medicine students with its 19 edition. He was the pioneered of radioisotope researches in animal biology in Turkey and was deemed worthy of various awards as a scientist. Noyan, who went down in history as the person who also designed and drew the occupational emblem of veterinary medicine used today in Turkey, is interested in poetry and painting. Conclusion: Biography studies of the elderly professionals who left their marks to the veterinary medicine have important place in history writings. Studying the biographies of elderly professionals and adding relevant courses to the curriculums can be suggested as they provide motivation and inspiration to the younger colleagues.